He-Plasma Jet Generation and Its Application for E. coli Sterilization - Liu, Tiejian; Zeng, Yuxuan; Xue, Xin; Sui, Yinyi; Liang, Yingying; Wang, Fushan; Feng, Fada (Journal of Spectroscopy, 2021)
Atmospheric pressure plasma jet (APPJ) is a promising technique for the sterilization of pathogenic microorganisms in an ambient environment. In this work, a helium-APPJ was generated by double dielectric barrier discharge and applied to the sterilization of model microorganism in air and water. Discharge characteristics (including waveform and frequency of applied voltage), jet properties (such as feed gas flow rate, jet length, thermal effect, and optic emission spectra), and sterilization performance (in terms of clear/sterilized area, size of plaques, and sterilization efficiency) were investigated. Homogeneous helium plasma jet was generated in an energy-efficient way (18 kHz, 6 kV, 0.08 W) with a 19 mm jet and limited heating. The He-APPJ achieved good sterilization performances within very short treatment time (as short as 30 s). For surface sterilization, the area of clear zone and size of the plaque were 1809 mm2 and 48 mm, respectively, within 5 min treatment. For water sterilization, 99.8% sterilization efficiency was achieved within 5 min treatment. The optic emission spectra suggest that active species such as excited molecules, ions, and radicals were produced in the He-APPJ. The as-produced active species played important roles in the sterilization process.